2018
DOI: 10.1016/j.humpath.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma with angioleiomyoma-like stroma and clear cell papillary renal cell carcinoma: exploring SDHB protein immunohistochemistry and the relationship to tuberous sclerosis complex

Abstract: Renal cell carcinoma (RCC) with angioleiomyoma-like stroma appears to be molecularly distinct from clear cell RCC; however, its relationship to clear cell papillary RCC remains debated. Recent studies have found that similar tumors sometimes occur in patients with tuberous sclerosis complex (TSC), of which 1 study found unexpectedly negative succinate dehydrogenase B (SDHB) immunostaining. We evaluated immunohistochemistry for SDHB in 12 apparently sporadic RCCs with angioleiomyoma-like stroma and correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Of note, this same RCCLS subtype has been documented to display aberrant Succinate Dehydrogenase B (SDHB) negativity on immunohistochemistry, similarly to the succinate dehydrogenase‐deficient RCC subtype, although in the absence of detectable deleterious SDHB genetic alterations that portend the development of SDHB‐deficient RCCs . Indeed, a recent study linked SDHB IHC signal rarefaction in RCCLS to decreased mitochondrial density as assessed by electron microscopy . As expected, no likely pathogenic or clearly pathogenic SDHB alterations were detected among our RCC samples studied via massive parallel sequencing.…”
Section: Discussionsupporting
confidence: 61%
“…Of note, this same RCCLS subtype has been documented to display aberrant Succinate Dehydrogenase B (SDHB) negativity on immunohistochemistry, similarly to the succinate dehydrogenase‐deficient RCC subtype, although in the absence of detectable deleterious SDHB genetic alterations that portend the development of SDHB‐deficient RCCs . Indeed, a recent study linked SDHB IHC signal rarefaction in RCCLS to decreased mitochondrial density as assessed by electron microscopy . As expected, no likely pathogenic or clearly pathogenic SDHB alterations were detected among our RCC samples studied via massive parallel sequencing.…”
Section: Discussionsupporting
confidence: 61%
“…Rare cases may show variant morphologies, reminiscent of clear cell or papillary RCC, and these were mostly detected in a tissue microarray (TMA) setting . It remains speculative whether these cases represent true SDH‐deficient RCCs due to germline or somatic SDH subunit gene alterations, or whether they show false‐negative SDHB staining, as documented in cases with clear cytoplasm and a paucity of mitochondria …”
Section: Sdh‐deficient Rccmentioning
confidence: 99%
“…To follow up and further investigate this observation, Williamson et al . evaluated 12 apparently sporadic ‘RCCs with angioleiomyoma‐like stroma’ for SDHB expression by using immunohistochemistry . They showed that the great majority of such cases actually showed at least focal and weak cytoplasmic staining for SDHB, and clarified that the apparent negative SDHB staining may be due to their clear or pale cytoplasm and decreased mitochondrial density.…”
Section: Rcc With Prominent Smooth Muscle Stromamentioning
confidence: 99%
See 2 more Smart Citations